PENERAPAN STRATEGI WORD TO MOUTH DALAM SISTEM JUAL BELI DI KELOMPOK PENGAJIAN SALAFI KOTA PEKANBARU - Genny Gustina Sari; Genny Ervina Gusti (LONTAR: Jurnal Ilmu Komunikasi, 2017)
Use shar'i hijab among Muslim today has become a phenomenon. Hijab syar'i not yet old-fashioned clothes and rigid model for a Muslim, is now so many models that mix and match colors and patterns so as to remove the effects of rigid and archaic that has been attached to the hijab syar'i. This phenomenon has been accompanied by the rise of online sales system is so attractive but informants in this study is still more favor with the Word of Mouth, By using the phenomenological theory of Alfred Schutz and the concept of Word of Mouth research results; communication Word of Mouth (WOM) is considered successful influence prospective buyers, because even if the purchase happens online, the kind of sales that berlangsusng a direct sales activities with direct marketing strategy. The purchase by Word of Mouth (WOM) is more interested in the Jemaah Salafi because they regard it as a Muslim woman and a sinner is a sinner misconduct. System on the basis of religious beliefs is what causes WOM strategy to be more effective, especially as the seller is a member of the Salafi school or at least use the hijab syar'i.Â Keyword : WOM, buy and sell, salafi